My house in Damascus : an inside view of the Syrian revolution - Darke, Diana (Haus Publishing, 2014)
How did Syria's revolution lose its way? 'My House in Damascus' illuminates the darker recesses not just of Syria's history and politics, but also of its society and secrets. Diana Dark's firsthand experience of Syria's many diverse communities explains why Syria was always a special case and why the Assad regime was never likely to collapse.